Eye movement desensitisation and reprocessing (EMDR) treatment associated with parent management training (PMT) for the acute symptoms in a patient with PANDAS syndrome: a case report - Cristiana A. Guido; Anna Maria Zicari; Marzia Duse; Alberto Spalice (BMC, 2019)
Abstract Background The purpose of this report was to present the results of eye movement desensitisation and reprocessing (EMDR) therapy associated with parent management training (PMT) in a child with paediatric autoimmune neuropsychiatric disorder associated with streptococcus (PANDAS), who had previously only been treated with pharmacological treatment. Case presentation The case concerns an 11-year-old boy who presented with simple and complex vocal tics, motor tics, obsessive-compulsive traits and irritability from the age of 6 years, in addition to a positive result for streptococcal infection. The course of symptoms followed a relapsing-remitting trend with acute phases that were contingent on the infectious episodes. Conclusions Following eight sessions of EMDR, preceded by training sessions with the parents, the child showed a significant reduction in symptoms and disappearance of the exacerbation. These results indicate the possibility of improving the treatment outcomes of patients with PANDAS by a combined approach using both antibiotic and EMDR therapies.